The effects of laparoscopic urologic surgery on cardiac functions: A pulse wave velocity study - Çiçek, Mehmet Çağatay (Turk J Urol, 2020)
OBJECTIVE: The aim of this study is to evaluate the effects of laparoscopic urologic surgery on cardiac functions by the parameter pulse wave velocity (PWV), a noninvasive method. MATERIAL AND METHODS: Between July 2012 and February 2013, a total of 47 patients were included in this prospective controlled study. Patients who have been scheduled for laparoscopic surgery (LS) (n=30) and open surgery (n=17) were enrolled in the study. Preoperative, perioperative, and postoperative cardiovascular parameters were measured by a PWV instrument, and the results were compared between laparoscopic (L) group and open (C) group. RESULTS: In the L group, compared to preoperative values, perioperative systolic arterial pressure, diastolic arterial pressure, and mean arterial pressure increased considerably, by 2.6%, 7.9%, and 4.7%, respectively. This was in contrary to reductions in these parameters by 9.5%, 5.7%, and 10%, respectively, in the C group. For the L group, cardiac output (CO) and cardiac index (CI) were increased in the perioperative period and decreased in the postoperative period. For the C group, there were no changes in measurements of perioperative and postoperative CO and CI. However, these changes in CO and CI were not significantly different between the L and C groups. Postoperative large artery elasticity index decreased in both groups. However, these changes did not represent significant difference between groups. CONCLUSION: Compared to open surgery, LS may cause increases in perioperative blood pressures. In addition, increased blood pressures may last even on the first postoperative day. These effects may be more important for patients with high cardiovascular risk.